NILAI-NILAI PENDIDIKAN KARAKTER CERITA RAKYAT NASAL SEBAGAI BAHAN AJAR BAHASA INDONESIA SMP KELAS VII - Monika Afriyanti; Emi Agustina; Amril Canrhas (Universitas Bengkulu, 2018)
This study aims to (1) describe the structure of fable and legend of the Nasal region, (2) to describe the educational values of fable characters and the legend of Nasal area and its relation with the material of class smp vii. This research uses descriptive qualitative method, the method is used to describe and analyze the structure of people's crita and the educational values of the character of Nasal society. Source of data in this research is informant. That is, citizens who provide information about all related to research. Data collection techniques in this study there are 3 namely: recording techniques, interview techniques and content analysis techniques The theory is used to analyze the structure of stories using structural theory. The results showed that the folklore of Nasal Kaur community consists of two types, namely legend and Fable. The value of character education found in the legend, that is independent. The value of character education found in fable stories, that is forgiving, ingenious, patient, friendly, hard work, willing to accept defeat. Based on 4 folk stories found, there is a story that can be used as a literary learning material in junior high school because it contains the moral value of education.Keywords: values of character education, folklore, structure